Analisis Kualitas Pelayanan Dinas Pemadam Kebakaran Kabupaten Garut - Ikeu Hikmawati (Penerbit Yayasan Daarul Huda Kruengmane, 2022)
In general, this research aims to analyze and describe the service quality of the Garut Regency Fire Department. The research uses a qualitative descriptive approach by emphasizing the concept of measuring service quality according to Dwiyanto's theory (2008:343-344), where the service quality of the Garut Regency Fire Department can be measured from the attitude of officers, procedures, time, facilities and services. The selection of informants was carried out by researchers purposively. Data collection is done by conducting interviews, observation and documentation studies. The results of the research show that in general the services of the Garut Regency Fire Department are of poor quality. Several problems were found, including the slow response time of officers, the speed and accuracy of fire extinguishing which was not optimal, the lack of fire service facilities and infrastructure and not all officers having received functional training, complaints from the public and public ignorance regarding the service complaint hotline available at the Fire Department. So it is recommended that fire fighters further increase response time and increase the speed and accuracy of service by overcoming obstacles that hinder service, proposing additions and rejuvenation of fire extinguisher operational facilities and infrastructure to local governments that are adjusted to the area, population and reach. services, involving all functional officers in functional technical training, responding to complaints or opinions expressed by the public, increasing public awareness by providing continuous and intensive education to the public about the dangers of fire both through print and electronic media.